Peptide-Carbon Quantum Dots conjugate, Derived from Human Retinoic Acid Receptor Responder Protein 2, against Antibiotic-Resistant Gram Positive and Gram Negative Pathogenic Bacteria - Mazumdar, Aninda; Haddad, Yazan; Milosavljevic, Vedran; Michalkova, Hana; Guran, Roman; Bhowmick, Sukanya; Moulick, Amitava (Nanomaterials (Basel, Switzerland), 2020)
Antibiotic-resistant bacterial infections have become global issues for public health, which increases the utter need to develop alternatives to antibiotics. Here, the HSER (Homo sapiens retinoic acid receptor) peptide was designed from retinoic acid receptor responder protein 2 of Homo sapiens, and was conjugated with synthesized CQDs (carbon quantum dots) for enhanced antibacterial activity in combination, as individually they are not highly effective. The HSER-CQDs were characterized using spectrophotometer, HPLC coupled with electrospray-ionization quadrupole time-of-flight mass spectrometer (ESI-qTOF) mass spectrometer, zeta potential, zeta size, and FTIR. Thereafter, the antibacterial activity against Vancomycin-Resistant Staphylococcus aureus (VRSA) and Escherichia coli (carbapenem resistant) was studied using growth curve analysis, further supported by microscopic images showing the presence of cell debris and dead bacterial cells. The antibacterial mechanism of HSER-CQDs was observed to be via cell wall disruption and also interaction with gDNA (genomic DNA). Finally, toxicity test against normal human epithelial cells showed no toxicity, confirmed by microscopic analysis. Thus, the HSER-CQDs conjugate, having high stability and low toxicity with prominent antibacterial activity, can be used as a potential antibacterial agent.
Keywords: carbon quantum dots; bacterial infections; antibiotic-resistant; antibacterial activity; toxicity